Prediction Method of Irregularity of High-speed Maglev Track Based on Normal Distribution Superposition Principle - Xin LIANG; Sansan DING; Chao HUANG; Dalian YU (机车电传动)
In order to predict for maglev track irregularity accurately, according to structure composition and technical characteristics of high-speed maglev track line, a irregularity fitting method of high-speed maglev track based on normal distribution superposition principle was applied. Based on the characteristic length of track (l=l 032 mm), the deviation characteristics was analyzed at the position of the length l, guide foundation length 3l, bridge 1/2 span length, span and 2 times span. The deviations of other non-nodes were fitted by linear interpolation method, the time domain track irregularity data was obtained by deviation superposition. Compared with the measured data, it was found that the irregularity of high-speed maglev track was obviously periodic, especially, the vertical irregularity had the same periodic frequency as the first order vertical bending of the bridge; In the short wave range (λ<5 m), the high-speed maglev spectrum was higher than the traditional wheel/rail spectrum. The range of medium and long waves of high-speed maglev was between the high speed ballastless spectrum in China and the low interference spectrum in Germany. The irregularity prediction method had general applicability to the line spectrum prediction of known construction technical requirement.